Elevated Synovial Fluid Concentration of Monocyte Chemoattractant Protein-1 and Interleukin-8 in Dogs with Osteoarthritis of the Stifle - Kleine, Stephanie A.; Gogal, Robert M.; George, Clinton; Thaliath, MaryAnn; Budsberg, Steven C. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Chemokines such as monocyte chemoattractant protein-1 (MCP-1) and interleukin-8 (IL-8) have been shown to cause monocyte and natural killer cell chemotaxis and polymorphonuclear cell chemotaxis, respectively. Additionally, MCP-1 signalling has been implicated in modulating pain. Elevated synovial fluid concentrations of MCP-1 and IL-8 have been demonstrated in humans with osteoarthritis, but currently there are no studies evaluating synovial MCP-1 or IL-8 concentrations in dogs. Additionally, there are no canine studies evaluating the correlation between these chemokines and caregiver perceived pain and mobility, as measured by the clinical metrology instrument, Liverpool Osteoarthritis in Dogs. This study documented elevated synovial fluid concentrations of IL-8 and MCP-1 in the stifle of dogs with secondary osteoarthritis compared with normal stifles. However, this study found no correlation between MCP-1 or IL-8 and Liverpool Osteoarthritis in Dogs or radiographic severity of osteoarthritis.
Keywords: inflammation; stifle; osteoarthritis